A proposed library resources and services marketing plan for the Armed Forces of the Philippines Main Library - Alunday, Wilvelyne B.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
Libraries in military camps need to market their resources and services not just to military personnel but also to the civilian residents. This study focused on the improvement of the current marketing efforts of the Armed Forces of the Philippines Main Library (AFPML) and on the awareness of the civilians and military personnel residents inside Camp General Emilio Aguinaldo about the AFPML's library resources and services.
An informal unstructured interview was conducted to be able to get clear information about the marketing efforts of the library. Based from the interview, budget and change of command are the main problems of AFPML when it comes to library marketing. However, the library was promotional to promote its resources and services and to attract more users.
A total of sixty-four (64) respondents were surveyed - fifteen Military Personnel (23.44%) and forty-nine civilians (76.56%). Most of the library users were Military Personnel (23.44%) and only few civilians (9.38%) know the AFP Main Library. The civilians are the family of Military Personnel who reside inside the military camp. The study found out that forty-three respondents (67.19%) do not know the existence of the Armed Forces of the Philippines Main Library. The data gathered revealed that library users are satisfied with the resources and services offered by the library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Armed Forces of the Philippines Main Library -- Marketing